The Human NK Cell Response to Yellow Fever Virus 17D Is Primarily Governed by NK Cell Differentiation Independently of NK Cell Education - Marquardt, Nicole; Ivarsson, Martin A; Blom, Kim; Gonzalez, Veronica D; Braun, Monika; Falconer, Karolin; Gustafsson, Rasmus; Fogdell-Hahn, Anna; Sandberg, Johan K; Michaëlsson, Jakob (The Journal of immunology (1950), 2015)
NK cells play an important role in the defense against viral infections. However, little is known about the regulation of NK cell responses during the first days of acute viral infections in humans. In this study, we used the live attenuated yellow fever virus (YFV) vaccine 17D as a human in vivo model to study the temporal dynamics and regulation of NK cell responses in an acute viral infection. YFV induced a robust NK cell response in vivo, with an early activation and peak in NK cell function at day 6, followed by a delayed peak in Ki67 expression, which was indicative of proliferation, at day 10. The in vivo NK cell response correlated positively with plasma type I/III IFN levels at day 6, as well as with the viral load. YFV induced an increased functional responsiveness to IL-12 and IL-18, as well as to K562 cells, indicating that the NK cells were primed in vivo. The NK cell responses were associated primarily with the stage of differentiation, because the magnitude of induced Ki67 and CD69 expression was distinctly higher in CD57(-) NK cells. In contrast, NK cells expressing self- and nonself-HLA class I-binding inhibitory killer cell Ig-like receptors contributed, to a similar degree, to the response. Taken together, our results indicate that NK cells are primed by type I/III IFN in vivo early after YFV infection and that their response is governed primarily by the differentiation stage, independently of killer cell Ig-like receptor/HLA class I-mediated inhibition or education.